The Oxford handbook of political economy (The Oxford handbooks of political science, 2006)
The Handbook views political economy as a set of methodologies, typically associated with economies, but now part and parcel of political science itself, that are used to explain political and economic phenomena at both the micro and macro level.. - As such, political economy becomes a grand, if incomplete, synthesis of the various strands of social science. Because institutions are often the subject matter of investigation, this approach incorporates many of the issues of concern to political sociologists and historians. Because political behavior and institutions are themselves a subject of study, politics becomes the subject of political economy. And because political economy also deals with the interaction between the political and economic spheres, economics itself can be seen as a special subset of the analysis. This handbook surveys the field of political economy, with 59 chapters ranging from national to international, institutional to behavioral, and methodological to substantive. Chapters on social choice, constitutional theory, and public economics are set alongside ones on voters and pressure groups, macroeconomics and politics, capitalism and democracy, and international political economy and international conflict.